Framing Dan Deep Linking Dalam Perspektif Hukum Hak Cipta Di Indonesia - budi agus riswandi (Jurnal Hukum IUS QUIA IUSTUM, 2006)
Framing and deep linking technology on the intemet which potentially to do a duplication and announcement raises copy right law problems in Indonesia. These problems raiseon the case of duplication and announcement without lisence. Besides that, the problems also raise on the law  announcement of copy rights in fregement related to framing and deep linking technology. Consequently, it is possibleto the Judgesto take different decision upon the case.